Croissance de l’opposition à la définition restrictive de la communauté d’expression anglaise - Quebec Community Groups Network (QCGN) (2021)

Opposition Grows to Restrictive Definition of English-speaking Community - Quebec Community Groups Network (QCGN) (2021)

Press Release : A Celebration in Song, Spoken Word & Step Final Episode of We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Making Homemade Tomato Sauce with Greg on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Author Conversations with Richard King on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Brief on Bill 96 : An Act Respecting French, the Official and Common Language of Quebec - Neal, Christopher; Barlow, Julie; Rodgers, Guy; Maturo, Nick (English-Language Arts Network (ELAN), 2021)

Brief on Bill 96 : An Act Respecting French, the Official and Common LAnguage of Quebec Submitted by the Quebec Writers' Foundation (QWF), The English Language Arts Network (ELAN), and the Quebec Drama Federation (QDF) - Quebec Writers' Federation (QWF); English Language Arts Network (ELAN); Quebec Drama Federation (QDF) (2021)
As part of Quebec’s English-speaking community, as artists, storytellers, dramatists and performers embedded in and contributing to Quebec’s cultural life, we are deeply troubled by the character, spirit and content of Bill 96, and the negative impact it threatens to have on Quebec’s English-language arts community.

Press Release : Organic Gardening with Hannah on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Urban Art with Jamie on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Tango Dancing with Mireille & Friends on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Making Jam with Susan on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : The Flamboyant World of Drag with Barbada on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Community Organization of Lanaudière (ECOL) (2021)

Press Release : Wine Pairing with Ana on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Horse Therapy with Karine on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Indigenous Hoop Dancing with Makhena on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Bird Watching with Joël Coutu on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Eating Healthy on a Budget with Crystal on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Animal Fostering with Cindy on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Spring Special! Gardening in Small Spaces on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Flower Arranging on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Laughter Yoga on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : New Episode of Web Series for Seniors We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : New York Times Bestselling Author Louise Penny Is The Guest of the Web Series for Seniors We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Celebrated New York Times Bestselling Author Louise Penny, on Senior’s Web Series We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Supporting Youth Mental Health in and through the Arts : An Evidence Base and Guide for Teaching Artists - Kukkonen, Tiina (2021)

Artcast Pilot Project : Compendium Version 1.0 - Webster, Daniel; Goddard, James; Jestin, Rio Victoria (English-Language Arts Network (ELAN), 2021)
The English Language Arts Network (ELAN) has been investing in providing solutions that help Quebec artists increase the value of their work on digital platforms. The ARTS2U project began in 2018 as a way for artists to achieve increased findability and discovery in the digital realm. As a result of the COVID-19 pandemic, ARTS2U project began including live broadcast events to arts event listings as of July 2020. The ARTSCAST Pilot Project addresses in depth details regarding inclusion and added value to live broadcasts to ARTS2U. In August and September of 2020, the ARTSCAST Pilot Project worked to add value to artist created digital media productions and packages. A series of nine events was assembled to test and document the potential to derive higher value and additional revenue streams. The events took place in multiple venues, featured multiple artists and disciplines and used a range of streaming technologies.